The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1207/s15326934crj1504_5
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Sources of Inspiration in Knitwear Design

Abstract: In an experimental study of designing by adaptation, professional and student knitwear designers were videotaped designing sweaters based on a Persian rug or a 19th century tapestry. The designers used a range of source-triggered and goal-directed adaptation strategies to create adaptations ranging from the closest possible translations into the medium to radical transformations of abstract characteristics. While each strategy sometimes led to each type of adaptation, the source-triggered strategies were predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 44 publications
1
22
0
3
Order By: Relevance
“…For example, Nagai and Taura (2006), Bonnardel and Marmèche (2004) and Linsey et al (2008) provided designers with stimuli and asked them to generate ideas that build on them, with the assumption that those that are more closely related to the sources are less creative. Eckert and Stacey (2003) provided expert and novice knitwear designers with a source of inspiration to analyse the differences between their approaches. They found that experts used their professional context, e.g.…”
Section: Case Study Methodologymentioning
confidence: 99%
“…For example, Nagai and Taura (2006), Bonnardel and Marmèche (2004) and Linsey et al (2008) provided designers with stimuli and asked them to generate ideas that build on them, with the assumption that those that are more closely related to the sources are less creative. Eckert and Stacey (2003) provided expert and novice knitwear designers with a source of inspiration to analyse the differences between their approaches. They found that experts used their professional context, e.g.…”
Section: Case Study Methodologymentioning
confidence: 99%
“…Each of Eckert and Stacey's (2003a) possible transformations were apparent in our research: (a) literal adaptation, (b) conscious simplification, (c) abstraction, (d) modification to source, and (e) association and deviation. Each of Eckert and Stacey's (2003a) possible transformations were apparent in our research: (a) literal adaptation, (b) conscious simplification, (c) abstraction, (d) modification to source, and (e) association and deviation.…”
Section: Transformations Of Inspirational Sourcesmentioning
confidence: 92%
“…Some inspirational sources are clearly connected to the final outcome, while others are connected to the creative process itself. These included (a) literal adaptation, (b) conscious simplification, (c) abstraction, (d) modification to source, and (e) association and deviation (Eckert and Stacey, 2003a). Sources of inspiration facilitate thinking, referencing, and practicing within the design process.…”
Section: Background: Influence Inspiration and Creativitymentioning
confidence: 99%
See 1 more Smart Citation
“…Garland and Barry (1992) in a recall study involving play diagrams presented to football experts, non-experts, and novices concluded that skilled performance required an immediate linkage of perceived patterns with conceptual categories in long-term memory. Eckert and Stacey (2003) concluded that garment designers first sought out patterns and then created memory units based on those patterns. Complex memories such as faces and stories could be reconstructed by combining a few key details in the pattern that stand out with stereotype elements filling in the remaining details.…”
Section: Literature Reviewmentioning
confidence: 99%